2002
DOI: 10.1006/dbio.2002.0754
|View full text |Cite
|
Sign up to set email alerts
|

GATA Proteins Identify a Novel Ventral Interneuron Subclass in the Developing Chick Spinal Cord

Abstract: Members of the GATA transcription factor gene family have been implicated in a variety of developmental processes, including that of the vertebrate central nervous system. However, the role of GATA proteins in spinal cord development remains unresolved. In this study, we investigated the expression and function of two GATA proteins, GATA2 and GATA3, in the developing chick spinal cord. We show that both proteins are expressed by a distinct subpopulation of ventral interneurons that share the same dorsoventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 37 publications
4
101
0
1
Order By: Relevance
“…It is unclear, however, at what developmental time these functionally distinct cell types emerge. Whereas V2 INs can be subdivided into two subtypes soon after they are born (Kuranaratne et al, 2002), postmitotic V1 INs appear to be genetically and morphologically homogeneous (Saueressig et al, 1999;M. Goulding, unpublished results), suggesting that V1 IN diversification may be a late event.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, however, at what developmental time these functionally distinct cell types emerge. Whereas V2 INs can be subdivided into two subtypes soon after they are born (Kuranaratne et al, 2002), postmitotic V1 INs appear to be genetically and morphologically homogeneous (Saueressig et al, 1999;M. Goulding, unpublished results), suggesting that V1 IN diversification may be a late event.…”
Section: Discussionmentioning
confidence: 99%
“…Chx10 in amniotes marks a subset of V2 neurons, called V2a neurons (Karunaratne et al, 2002). We have revealed that alx marks ipsilateral descending neurons that provide excitation to motoneurons during locomotion.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, mechanisms that increase the initial diversity of neuronal subtypes are also likely to operate. For example, the expression of additional transcription factors divides the V2 neuron population into two spatially intermixed groups of neurons that appear to be generated in the same region of the spinal cord (Karunaratne et al 2002;Smith et al 2002). Nevertheless, examining the generation of MNs and V0-V3 neurons serves as a powerful experimental paradigm for exploring the mechanisms that control the spatial allocation of neuronal subtype identity.…”
Section: Gli Repressionmentioning
confidence: 99%